ІННОВАЦІЙНИЙ РОЗВИТОК КРАЇНИ ЯК РУШІЙНИЙ ЧИННИК ПІДВИЩЕННЯ НАЦІОНАЛЬНОЇ КОНКУРЕНТОСПРОМОЖНОСТІ - Kovpaka, Anastasiya (Zhytomyr Ivan Franko State University, 2021)
This publication is devoted to highlighting the problem of ensuring the appropriate level of national competitiveness and identifying ways to increase it in today's competitive market environment. In the context of the study, the main reasons for Ukraine's chronic lag in the system of international economic relations were identified, including: irrational use of the country's resource potential, high material consumption, energy-intensive economy, low efficiency of economic reforms, physical and moral depreciation, lack of sufficient funding for research and development, high unemployment and the progressive trend of emigration of scientists, unfavorable investment climate and others. According to the main factors used by the world community in determining the growth of competitiveness of the economy, three groups of indicators were identified, which are the main competitive advantages in an unstable market economy, namely: factors of production, income and investment and innovation potential. It was possible to analyze the indicators of the human development index and the level of competitiveness of the country on the basis of data from the International Institute for Development Management and the UNDP Report. Indicators of Ukraine in the ranking of innovative economies of the world helped to determine the main causes of technological backwardness of the country, based on which the main directions of innovation development were proposed: state support of science-intensive production, reorientation of raw materials orientation of Ukraine's exports to conduct innovative business. Attracting investment in technology development and innovative development of enterprises, stimulating the production of high-tech products and compliance with quality standards are the most important steps towards the reorientation of Ukraine's economy to an innovative model of socio-economic growth.